Curriculum Restructuring and Reorientation of the Islamic Religious Education Study Program in the Digital Era - Wildan Nur Hidayat; Wildan Murtadho; Marlena; Aisyah Sarika; Apri Lozi (Yayasan Azhar Amanaa Yogyakarta, 2025)
Technological disruption in the Society 5.0 era has triggered a shift in religious authority to virtual spaces and created a significant gap within the conventional curriculum of the Islamic Religious Education (PAI) Study Program, which remains rigid and lacks technology integration. Employing a qualitative literature review approach with content analysis, this study elaborates on macro-policy reconstruction strategies for the PAI curriculum based on Outcome-Based Education (OBE) and blended learning. This reconstruction integrates pure Islamic sciences (ulûm al-dîn) with data literacy, technology, and contemporary science without diminishing fundamental religious subjects. This transformative-digital curriculum reorients the philosophical direction of graduates, enabling them to adaptively serve as Islamic education content creators, cyber counselors, and pioneers of religious moderation in the digital sphere. The synergy between updating formal technological aspects and internalizing Islamic spiritual values (core values) serves as the primary key to producing PAI graduates who are competent, competitive, and highly principled in the global era.